(untitled) (CIPEEX, 2025)
Rabies is a viral zoonosis known since ancient times, with historical records indicating an association between dog bites and the occurrence of the disease. In Brazil, rabies is a public health concern due to its high lethality, which reaches approximately 100% when untreated, and its transmission through mammals, especially dogs, cats and bats. The disease has a variable epidemiological behavior and is endemic in specific regions of the country. The aim of this study is to describe the profile of human anti-rabies care in the municipality of Ceres, Goiás, between 2017 and 2021, analyzing the epidemiological data and characteristics of rabies-related incidents. The research is descriptive in nature, based on the analysis of secondary data obtained from human rabies care records registered in the Notifiable Diseases Information System (SINAN). All the treatments carried out in the municipality of Ceres were included, taking into account variables such as the type of exposure, the species of the attacking animal, the location and severity of the injuries, and the condition of the animal after the observation period. Between 2017 and 2021, 498 anti-rabies cases were recorded in Ceres, with the majority of attacks (82.12%) being caused by dogs. Between 2017 and 2021, 498 anti-rabies cases were recorded in Ceres. The majority of attacks were caused by dogs (82.12%), with bites being the most common type of exposure, accounting for 72.69% of cases. The analysis also revealed that hands and feet were the most affected anatomical regions. The number of cases varied over the years, with a notable increase in 2021, possibly associated with the anti-rabies vaccination campaigns held in September and October, which coincided with the highest number of notifications. The data suggest that vaccination and surveillance campaigns play a crucial role in rabies control in the municipality of Ceres. The predominance of dog bites underlines the need to intensify educational and animal control actions. Furthermore, the observation of an increase in notifications during the months of the national vaccination campaign indicates the importance of maintaining these initiatives as a strategy for rabies prevention. The study reinforces the ongoing need for epidemiological surveillance and post-exposure prophylaxis to minimize the risk of human rabies transmission in the region. Post-exposure prophylaxis remains essential to prevent fatal cases, highlighting the importance of health education and rapid response to incidents involving potentially infected animals.